Secondary Traumatic Stress and Resilience of the Nurses at the Psychiatric Centers in Tehran City, Iran - E Jafar Jalal; F Aziz Mohammadi; N Seyyed Fatemi; H Haghani (Iran University of Medical Sciences, 2019)
Background & Aims: Secondary traumatic stress could be described as an occupational hazard for those providing care to victims of trauma. Nurses in psychiatric wards are faced with severe and complicated challenges in the workplace to provide mental health care. Resilience and the associated behaviors help overcome negative experiences and turn them into positive experiences. The present study aimed to investigate secondary traumatic stress and resilience in the nurses at the psychiatric medical centers affiliated to Tehran University of Medical Science in 2018. Materials & Methods: This cross-sectional, descriptive study was conducted on 200 nurses engaged in the psychiatric medical centers affiliated to Iran University of Medical Sciences, Shahid Beheshti University of Medical Sciences, and Tehran University of Medical Sciences. The participants were selected via stratified proportional allocation and convenience sampling. Data were collected using the secondary traumatic stress questionnaire and resilience scale. Data analysis was performed in SPSS version 16. Results: In total, 30%, 21.5%, and 26% of the nurses reported high and severe, moderate, and mild secondary traumatic stress. The mean score of secondary stress was 37.64 ± 10.03 69.71 ± 13.63. Conclusion: According to the results, the mean score of secondary stress was moderate in the nurses, while the mean score of resilience was above the median of the questionnaire. The adoption of strategies such as the reduction of workload, increased staff oversight, and improvement of staff support are recommended for the management of secondary traumatic stress. Furthermore, the resilience of psychiatric nurses could be enhanced through proper physical and mental health management and promotion of mental health in these healthcare providers.